Occurrence of pneumocystis pneumonia in HIV-infected patients and the interference of the highly active antiretroviral therapy - Barbosa, Alexandre Naime [UNESP]; Souza, L. R. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
From the beginning of the AIDS epidemic, pneumocystis pneumonia ( PCP) has been distinguished as one of the most frequent opportunistic diseases with high morbid-mortality. As from 1996, the advent of the highly active antiretroviral therapy ( HAART) has changed the characteristics of such epidemic by reducing its related diseases and, as a result, AIDS-related mortality. With the purpose to estimate PCP occurrence and HAART interference, 376 HIV-infected or AIDS patients were studied from January 1992 to December 2002. Among them, 58 ( 15.5%) PCP cases were found. There was a higher occurrence of PCP in the group of patients in which HAART was not used, with 40 ( 69.0%) of the episodes. As regards the studied period, a tendency to a linear reduction in annual PCP incidence was observed. The mean of T CD4+ lymphocytes in the patients with PCP ( 117 cells/mm(3)) was significantly lower when compared to that of the other individuals ( 325 cells/mm(3)). Therefore, this study suggests a temporal reduction in PCP occurrence related to HAART use with higher T CD4+ lymphocyte counts. Nevertheless, this opportunistic infection still shows significant incidence in AIDS patients. ( NCT00516581).
Keywords: AIDS; pneumocystis pneumonia; antiretroviral treatment; T CD4+ lymphocytes